2011
DOI: 10.3899/jrheum.110558
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Remitting Seronegative Symmetrical Synovitis with Pitting Edema Compared to Patients with Pure Polymyalgia Rheumatica

Abstract: Despite evidence that RS3PE is clinically distinct from PMR, we observed characteristics, treatment response, and outcomes like those expected in pure PMR. Compared to patients with pure PMR, patients with RS3PE are more likely to be male, to be depressed, and to smoke. Contrary to earlier studies, no clear association of RS3PE with malignancy was found despite rigorous cancer screening, although clinicians should be aware that patients with concurrent cancer may manifest more systemic signs and symptoms, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
0
30
0
5
Order By: Relevance
“…[3,4] S›kl›kla geriatrik popülas-yonda ve erkeklerde kad›nlardan daha s›k olarak görül-mektedir. [5,6] Etiyolojisi aç›k olmamakla birlikte az say›da olgu ile yap›lan çal›flmalarda interlökin (IL)-6 düzeylerinin yük-sek bulunmas› inflamasyonun rolünü ortaya koymaktad›r. [7] Ayr›ca potent bir vazodilatatör olan ve damar geçir-genli¤ini artt›ran 'vaskular endotelyal büyüme faktörü' (VEGF) düzeyleri, RS3PE'li hastalarda kontrol grubuna göre anlaml› düzeyde yüksek bulunmufltur.…”
Section: Tart›flmaunclassified
See 1 more Smart Citation
“…[3,4] S›kl›kla geriatrik popülas-yonda ve erkeklerde kad›nlardan daha s›k olarak görül-mektedir. [5,6] Etiyolojisi aç›k olmamakla birlikte az say›da olgu ile yap›lan çal›flmalarda interlökin (IL)-6 düzeylerinin yük-sek bulunmas› inflamasyonun rolünü ortaya koymaktad›r. [7] Ayr›ca potent bir vazodilatatör olan ve damar geçir-genli¤ini artt›ran 'vaskular endotelyal büyüme faktörü' (VEGF) düzeyleri, RS3PE'li hastalarda kontrol grubuna göre anlaml› düzeyde yüksek bulunmufltur.…”
Section: Tart›flmaunclassified
“…Çeflitli serilerde ortalama malignite oran› %7-31 aral›¤›nda bildirilmifltir. [5] Bu veri RS3PE'li hastalardaki malignite insidans›n›n normal populasyona oranla önemli oranda yüksek oldu¤unu desteklemektedir. Ancak RS3PE'li hastalarla ilgili genifl olgu serileri olmad›¤›ndan bu hastalardaki gerçek malignite insidans› bilinmemektedir.…”
Section: Tart›flmaunclassified
“…2,3,6,9,10 A study from Kimura et al in 2012 revealed that all studied patients with RS3PE met PMR criteria, an unexpected finding. 10 PMR is characterized by inflammatory pain and stiffness of the shoulder and pelvic girdles, with biochemical evidence of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively acute onset of symmetrical inflammation of joints and carpal tunnel syndrome are overlapping features. 10 However, RS3PE syndrome is more common in men, involving the wrist, carpus, and flexor digitorum tendons disproportionately, and is associated with marked pitting edema of the dorsum of the hand. In contrast, PMR is more common in women, predominantly involving the shoulders and hips.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation